Analyzing GPT-4 misinterpretations of russian grammatical constructions - Plotnikov, Timofei (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2024)
Generative Pre-trained Transformers (GPTs), which are Large Language Models (LLMs) primarily trained on datasets dominated by English texts, can incorporate inaccuracies into their final outputs. The training data bias presents challenges for accurate performance in non-Roman script languages, such as Russian. Challenges are specifically expected with grammatical constructions in Russian which are colloquial, idiomatic, and non-compositional. Although the empirical investigation reveals that, overall, GPT-4 performs well with the majority of Russian grammatical constructions, it still encounters limitations with low-frequency constructions due to insufficient training data, a lack of context, and the influence of the English language.